The Protection of Intellectual Property Rights in Innovative Projects - Khantarjian, Sarkis; Nahapetyan, Seda (Bulletin of Yerevan University G: Economics, 2016)
The article notes that, along with the adoption of laws on intellectual property rights protection in Armenia there are no laws to assess their value. It is estimated in the organizations involved in the assessment of real estate, which is unacceptable. The description of the experience of advanced countries is presented.
Keywords: objects of intellectual property, protection of rights, innovative projects